2000
DOI: 10.1016/s0735-1097(00)00694-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical behavior of T-Wave polarity alternans in patients with congenital long QT syndrome

Abstract: The TWPA was dependent on the cardiac CL; there was loss of the LncQT/CL and an increase in the QT interval variability. Like other biological variables, T-wave polarity alternans has a higher density during the morning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The Ca 2+ channel blocker verapamil reduced these alternans, suggesting an involvement of intracellular Ca 2+ deregulation in this phenomenon. Previous studies had shown that patients with long QT syndrome can exhibit T-wave alternans during sinus tachycardia (Cruz Filho et al, 2000; Viskin et al, 2004). …”
Section: Models For the Lqt3 Syndromementioning
confidence: 98%
“…The Ca 2+ channel blocker verapamil reduced these alternans, suggesting an involvement of intracellular Ca 2+ deregulation in this phenomenon. Previous studies had shown that patients with long QT syndrome can exhibit T-wave alternans during sinus tachycardia (Cruz Filho et al, 2000; Viskin et al, 2004). …”
Section: Models For the Lqt3 Syndromementioning
confidence: 98%
“…Macroscopic TWA has frequently been reported in patients with LQTS: 2.5% in standard 12‐lead ECGs 8 and 45% in ambulatory ECGs. 15 Macroscopic TWA is not only the diagnostic criteria for LQTS but also a risk marker for cardiac events. 8 Due to the process of spatially discordant repolarization alternans, in which adjacent myocytes begin alternating in opposing phases, the presence of TWA in patients with LQTS can predispose to Tdp.…”
Section: Discussionmentioning
confidence: 99%
“…Macrovoltage TWA has been shown to precede episodes of polymorphic ventricular tachycardia in patients with LQTS (Schwartz et al, 1975), and the presence of macrovoltage TWA at rest seems to be an adverse prognostic factor (Cruz Filho et al, 2000; Fujimoto et al, 1999; Motoyasu et al, 1992; Shimizu et al, 1996). In another study, μV-TWA was only infrequently found and no significant differences were detectable comparing patients with or without LQTS (Kaufman et al, 2001).…”
Section: Discussionmentioning
confidence: 99%